2000
DOI: 10.1007/pl00001813
|View full text |Cite
|
Sign up to set email alerts
|

Role of surface chemical signals in egg cannibalism and intraguild predation in ladybirds (Coleoptera: Coccinellidae)

Abstract: Summary. The eggs of some ladybirds are known to be toxic to intraguild ladybird predators. However, this defence is of little value if the eggs are killed before their toxicity becomes apparent. The results presented in this paper indicate that chemicals on the surface of the eggs of two species of ladybirds signal the relative risk of cannibalism and intraguild predation. In Adalia bipunctata and Coccinella septempunctata, 87% of the chemicals are alkanes. Each species of ladybird is less reluctant to eat th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
87
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 27 publications
(20 reference statements)
3
87
0
2
Order By: Relevance
“…This finding is in line with the observation that the alkaloids of A. bipunctata are less toxic than those of C. septempunctata (De Jong et al, 1991). Recently, Hemptinne et al (2000) noted that such a defence is of little value if the eggs are killed before their toxicity becomes apparent. Our own direct observations, however, suggest that the toxicity of coccinellid eggs becomes apparent early enough for T. brassicae females to lead to a low probability of parasitisation under field conditions.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding is in line with the observation that the alkaloids of A. bipunctata are less toxic than those of C. septempunctata (De Jong et al, 1991). Recently, Hemptinne et al (2000) noted that such a defence is of little value if the eggs are killed before their toxicity becomes apparent. Our own direct observations, however, suggest that the toxicity of coccinellid eggs becomes apparent early enough for T. brassicae females to lead to a low probability of parasitisation under field conditions.…”
Section: Discussionsupporting
confidence: 83%
“…Thus far, few egg parasitoids have been reared from coccinellids and these scarce records did not include Trichogramma (Hodek & Honek, 1996). The reason may be that eggs, like other stages of coccinellids, are chemically defended (e.g., Agarwala & Dixon, 1992;Hemptinne et al, 2000). Our results indicate that the eggs of A. bipunctata are less deterrent to T. brassicae than eggs of C. septempunctata.…”
Section: Discussionmentioning
confidence: 63%
“…Soares & Serpa (2006) have observed no oviposition in Coccinella undecimpunctata L. in the presence of adult H. axyridis, but the reverse in case of conspecific adults. Females of C. sexmaculata are known to lay fewer eggs in the presence of an immobilized conspecific adult female (Agarwala et al, 2003), whereas C. septempunctata does not oviposit in the presence of conspecific adult females (Hemptinne et al, 1993). Mishra & Omkar (2006) have also shown inhibitory effects of female conspecific presence and semiochemicals in P. dissecta.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies discuss the role of egg (Hemptinne & Dixon, 1991;Hemptinne et al, 1993), pupal (Hemptinne & Dixon, 1991) or adult presence (Hemptinne et al, 1992(Hemptinne et al, , 1993Mishra & Omkar, 2006) and/or their semiochemicals in influencing oviposition (Doumbia et al, 1998;Mishra & Omkar, 2006). Previous studies have found no influence of egg and pupal presence on oviposition (Hemptinne & Dixon, 1991;Hemptinne et al, 1993). Adult ladybirds known to leave tracks include Epilachna vigintioctomaculata, Epilachna vigintioctopunctata (Fabricius) and C. septempunctata (Kosaki & Yamaoka, 1996;Nakashima et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation